Volatile capital flows and economic growth: The role of banking supervision - Neanidis, Kyriakos C. (Journal of Financial Stability, 2019)
In this paper, we examine the links among banking supervision, the volatility of financial flows, and economic growth. In particular, we explore whether banking regulation mitigates the adverse effects of capital flows volatility on economic growth. Using cross-country data over four decades, we find that banking supervision promotes economic growth by dampening the negative impact of volatile capital flows. The findings hold for both aggregate capital flows and its various components, and for both its net and gross counterparts, while they are also robust for various indicators of regulatory policies. The results support the argument that bank regulatory policy rules designed to ensure financial stability are beneficial to long-run economic growth.